Birth Weight With Stunting Incidence In Infants Aged 6-24 Months - Niar; Hadriyani Amin; Sumiyati; Ariani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Background: Riskesdas 2013 data for short and very short toddlers was 37.2% while in 2018 it decreased to 30.8%. Although this short and very short toddler has decreased, the amount of 30.8% is still very high Objective: To find out the relationship between low birth weight and the incidence of stunting in infants aged 6-24 months in the working area of ​​the Rantepuang village kecamatan Sesenapadang Mamasa District Types of research :. This research was carried out descriptive analytical, namely research that tried to explore how health phenomena occurred using a cross sectional approach Samples: samples in this study were 33 infants aged 6-24 months in Rantepuang Village, Sesenapadang District. The results of the study: from the results of the test analysis with Fisher's exact test obtained a significance value of 0.023 and odds ratio 18,75. Conclusion: There is a relationship between Baby’s birth weigh and Stunting incidence in infants age 6-24 months